(untitled) (Bangladesh Journal of Endosurgery, 2013)
Twenty-nine children with suspected gastroesophageal reflux disease (GERD) and 17 children as a reference group were enrolled in the study. A conventional white light endoscopy of the oesophagus was supplemented by a probe-based confocal laser endomicroscopy (pCLE) and followed by a biopsy for histological examination. A comparative analysis of endoscopic, endomicroscopic, and histological data were performed. The pCLE allows detecting oesophagitis with the sensitivity and specificity of 93% and 94%, respectively; gastric and intestinal metaplasia typical for Barrett oesophagus with 83% and 100%, respectively; and polyps of the cardioesophageal passage with the sensitivity of 89% in patients with long-term GERD. Thus, this method allows taking an optical biopsy of pathological changes of esophageal mucosa just during the standard endoscopic investigation. DOI: http://dx.doi.org/10.11593/bje.2013.0102.0012 Bangladesh Journal of Endosurgery Vol.1(2) May 2013: 1-6